ZRZECZENIE SIĘ PRAWA DO WNIESIENIA APELACJI W POSTĘPOWANIU UPROSZCZONYM - Kincbok, Agnieszka (Zeszyty Prawnicze, 2017)
Renunciation of the Right of Appeal in the Simplified Procedure Summary This aticle concerns the institution of renunciation of the right of appeal, which is regulated by article 5058 § 3 of the Act of 17 November 1964 - Civil Proceedings Code (CPC). Renunciation of the right of appeal, which was introduced to the Polish civil procedure by an amendment to the CPC of 24 May 2000, functions only in the simplified procedure. In consequence it is impossible to renounce the right of appeal both in the standard procedure based on the general regulations and in the remaining types of procedures under CPC. This paper addresses the questions of who is authorized to renounce ius appellandi, when and in what form this can be done. Moreover this article discusses whether under article 5058 § 3 of CPC the judge is authorized to decide that renunciation of appeal is unacceptable for reasons specified in articles 203 § 4, 469 and 47913 of the CPC. The author of the article argues that on the ground of the currently binding regulations the judge does not have this kind of prerogative. The article also discusses procedural effects of the renunciation, which are different depending on the party making such declaration. Finally, this article looks into the widely disputed issue whether it is possible to cancel the declaration of renunciation of ius appellandi.